Using Conceptual Metaphor To Help Children in Understanding Corona Virus Pandemic : Cognitive Semantic Approach - Susiyanti Rusyan; Ervina CM Simatupang; Dianita Dianita; Atri Nadia (Universitas Cokroaminoto Palopo, 2022)
The Coronavirus (COVID-19) has brought suffering to almost people around the world. These situations lead people of all ages to take steps to protect themselves from the virus, including children. They need to learn about the virus that affects them and their community. Among the learning resources of Coronavirus to be learned by children, the researchers find the use of conceptual metaphors depicting the virus. Using the descriptive qualitative analysis and cognitive semantics approach, this article aims to analyze how Coronavirus is depicted through the conceptual metaphors. The data is taken from learning resources which are electronic books (e-book) and video published on Social Media. In analyzing the data, the researchers use the Conceptual Metaphor Theory (CMT) proposed by Lakoff and Johnson (1980) and the mapping theory by Langacker (1987). The research results show that (1) the Coronavirus is mainly depicted as A HUMAN, and (2) COVID-19 Pandemic is also depicted as A WAR. The use of conceptual metaphor is helpful to help children understand the complex ideas about Coronaviruses in simple terms and to help them understand what is happening. The use of conceptual metaphors also will help the parents and caregivers explain the Coronavirus to children.